Modeling The Generation And Attractiveness Of Passenger Demand Trips On The Madiun-Slahung Railway Reactivation Line - Leliana, Arinda; Imron, Nanda Ahda; Handoko, Handoko; Puspitasari, Armyta; Oktaviastuti, Blima (Universitas Negeri Semarang, 2023)
The reactivation plan of the Madiun-Slahung railway line in the National Railway Master Plan is the main program for the development of the railway network and service stage IV in 2026-2030, therefore it is necessary to conduct research on the demand for traction and generation as well as passenger interest in the future Madiun- This shelters are reactivated. Based on the results of data analysis and discussion of the calculation of the Madiun-Slahung area, it can be concluded that the model of the reactivation area of the Madiun-Slahung railway covers 7 districts, consisting of 45 sub-districts/villages. The method used is a household survey (Household Interview) which is intended to produce data on travel patterns and characteristics that affect the trip. The number of trip generation occurs in the range of numbers 6939-22594 motorbikes/hour for trip production and 1123-52265 motorbikes/hour for trip attraction, where zone 2, Kartoharjo sub-district has the largest number of trip production and zone 4, Ponorogo sub-district has the largest number of trip attractions. This is due to the high population, number of vehicle ownership and the strength of attraction due to the large number of shops and campuses and schools in the zone. The largest travel distribution value occurs in zone 4, because the zone is land use for shops, offices, campuses and schools.